Relationship between family characteristics and sex offences by young males - Guzman Castillo, Berenice (2016)
The aim of this paper is to explore the relationship between family characteristics and young sex offenders. The analysis used draws upon data from juvenile delinquents in the England's secure Youth Treatment Service in 1999, containing 126 males between 11 and 17 years old. A binary logistic regression analysis was conducted to ascertain the relationship of family factors (i.e., family structure, domestic violence, criminality, alcohol and drugs misuse, and psychiatric illness) on the likelihood that adolescents become sex offenders. Results suggest that all variables used in the logistic regression model were associated with committing a sex offence, except foster care, which reveals that foster placements are a protective factor related to sexual offending behaviours. Additional findings and implications are discussed.